Exploring Tax Avoidance In Indonesian Energy Companies Between 2018-2022 - Koerniawan, Koenta Adji; Zahrah, Delfira Mutia (SEAN Institute, 2024)
Taxes are essential for national development, but they can also tempt companies to avoid paying their fair share. Although legal, aggressive tax avoidance raises concerns about declining tax income and hindered development. This study investigates the impact of transfer pricing, CEO tenure, and indications of fraudulent financial reporting on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. This research uses a combination of quantitative, verification and descriptive approaches to determine its effect by analyzing secondary data. Utilizing panel data regression analysis, the research explores the extent to which these variables influence tax avoidance practices. Samples were obtained from 27 companies with a total of 135 observation data using purposive sampling techniques, then analyzed using panel data regression with Eviews 12 software. Partially, the findings reveal that transfer pricing has a positive effect on tax avoidance, while CEO tenure and indications of fraudulent financial reporting have no effect on tax avoidance. Empirical findings indicate that transfer pricing has a significant impact on tax avoidance behavior, while CEO tenure and indicators of fraudulent financial reporting do not exhibit substantial effects. Specifically, the results suggest that companies employ transfer pricing strategies to avoid taxes and reduce their tax burden. Additionally, the length of a CEO's tenure and the presence or absence of indicators of fraudulent financial reporting do not consistently determine whether a company engages in tax avoidance. However, all three variables simultaneously influence tax avoidance. This study contributes to the broader understanding of tax avoidance dynamics within the energy sector, providing a foundation for future research and policy formulation.